2015
DOI: 10.1021/acsami.5b04652
|View full text |Cite
|
Sign up to set email alerts
|

Si/Ti2O3/Reduced Graphene Oxide Nanocomposite Anodes for Lithium-Ion Batteries with Highly Enhanced Cyclic Stability

Abstract: Silicon (Si) has attracted tremendous attention as a high-capacity anode material for next generation Li-ion batteries (LIBs); unfortunately, it suffers from poor cyclic stability due to excessive volume expansion and reduced electrical conductivity after repeated cycles. To circumvent these issues, we propose that Si can be complexed with electrically conductive Ti2O3 to significantly enhance the reversible capacity and cyclic stability of Si-based anodes. We prepared a ternary nanocomposite of Si/Ti2O3/reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…15b and c shows galvanostatic cycling and the rate capability respectively. Besides various rGO based composites like (i) crumpled rGO/MoS 2 nanoflowers, 172 (ii) amorphous GeO x -coated rGO balls, 173 (iii) copper sulfide nanowires/rGO, 174 (iv) Si/Ti 2 O 3 /rGO, 175 (v) MnS hollow microspheres-rGO, 176 (vi) copper silicate hydrate hollow spheres-rGO 177 (vii) fluorine-doped tin oxide nanocrystal/rGO, 178 (viii) hollow nanobarrels of α-Fe 2 O 3 on rGO 179 and (ix) hierarchical rGO-Co 2 V 2 O 7 nanosheets 180 etc. shows an improved performance and stability as anode material for the lithium-ion batteries.…”
Section: Lithium Ion Battery Application 511 Anode Materialsmentioning
confidence: 99%
“…15b and c shows galvanostatic cycling and the rate capability respectively. Besides various rGO based composites like (i) crumpled rGO/MoS 2 nanoflowers, 172 (ii) amorphous GeO x -coated rGO balls, 173 (iii) copper sulfide nanowires/rGO, 174 (iv) Si/Ti 2 O 3 /rGO, 175 (v) MnS hollow microspheres-rGO, 176 (vi) copper silicate hydrate hollow spheres-rGO 177 (vii) fluorine-doped tin oxide nanocrystal/rGO, 178 (viii) hollow nanobarrels of α-Fe 2 O 3 on rGO 179 and (ix) hierarchical rGO-Co 2 V 2 O 7 nanosheets 180 etc. shows an improved performance and stability as anode material for the lithium-ion batteries.…”
Section: Lithium Ion Battery Application 511 Anode Materialsmentioning
confidence: 99%
“…Figure a displays the survey XPS spectrum of the composite; the Ti 2 p peak is observed in addition to peaks of silicon and oxygen, which indicates that the titania‐54.3 %‐silicon composite consists of titanium, silicon, and oxygen. A high‐resolution O 1 s XPS spectrum of the titania‐54.3 %‐silicon composite (Figure b) shows two peaks at 530.0 and 532.4 eV, which are attributed to Ti−O and Si−O, respectively . The high‐resolution spectrum of the Si 2 p region of the sample is shown in Figure c; the peaks located at 99.9 eV are indexed to metallic silicon, and the two other peaks located at 100.9 and 103.0 eV are indexed to silicon oxide (SiO x , x <2; and SiO 2 ) owing to the oxidation of silicon nanoparticles in air .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, volume changes of silicon nanoparticlesd uring repeated charge/discharge processes, when employed as anode materials for LIBs, could be largely suppressedo wing to the buffering effect of the titania coating layer on the silicon nanofiber surfaces, and enhanced electrochemical performance could be obtained. Moreover,t he original hierarchical network structures of the cellulose substance are maintained in the sample, whichp rovide enough space to accommodate the seriousv olume change of the anode upon cycling, and facilitate the electrode- [67] The high-resolution spectrumo ft he Si 2p region of the sample is shown in Figure 3c;the peaks located at 99.9 eV are indexed to metallic silicon, and the two other peaks located at 100.9 and 103.0 eV are indexed to silicon oxide (SiO x , x < 2; and SiO 2 )o wing to the oxidation of silicon nanoparticles in air. [23,26,68] This silicon oxide layer could serve as ab uffer layer for volumec hanges to the silicon nanocrystals upon charge/discharge cycles when the composite is employed as the anode of LIBs.…”
Section: Resultsmentioning
confidence: 99%
“…[74] The thermal-reduced graphene-based materials were widely researched and applied to obtain low-defect graphene for energy storage devices. This led to excellent improvement in electrochemical performance of such devices as Li-ion batteries (LIBs), [55,[75][76][77][78][79][80][81][82][83][84] Li-air batteries, [85][86][87][88] Li-sulfur batteries (LSBs), [89] Na-ion batteries (SIBs), [81,90] Al-ion batteries (AlBs), [47][48][49][50] and SCs. [91] Zhang et al [83] used graphite oxide (GO) and triphenylphosphine (TPP) as carbon and phosphorus sources for synthesizing phosphorus-doped graphene (PG) by thermal annealing reduction (e.g., 1000°C).…”
mentioning
confidence: 99%
“…The crumpled RGO and carbon fiber formed a dual continuous electronic transport network (Figure 2b), improving the electronic conductivity and the void spaces in crumpled RGO ensure the effective stress releasing and volume buffering, all of these resulted in a high reversible capacity (1225 mAh g À1 ) and excellent cycling stability (Figure 3c). Park et al [82] For preparing high-quality graphene, high-temperature annealing was necessary, which helped repair the defects in RGO to obtain well-structured graphene materials. Chen et al [55] firstly reported a high-quality RGO film with an electrical conductivity of up to 3112 S cm…”
mentioning
confidence: 99%